The big society: Rediscovery of 'the social' or rhetorical fig-leaf for neo-liberalism?. (August 2013) - Corbett, Steve; Walker, Alan
This paper subjects to critical scrutiny the idea of the 'big society' which, at present, is the UK Coalition government's big idea and the personal mission of the Prime Minister David Cameron. First of all the concept is explained, with reference to some of the rhetoric surrounding it. Then the philosophical foundations of the 'big society' are unpacked, with particular reference to Red Toryism and libertarian paternalism. This is followed by an assessment of the big society and reference to the other major plank in the government's social policy agenda, large cuts in public expenditure, that reflects the neo-liberal engine driving the strategy – the hollowing-out of the state – which has implications for the community initiatives and NGOs favoured by the big society's promoters but which are entirely unacknowledged by them. Then a comparison is made between the present big society idea and Margaret Thatcher's denial of the existence of society, which reveals many similarities in substance despite the rhetorical distancing. The final part of the paper examines the parallel Blue Labour analysis and suggests an alternative participatory democratic approach.